Exploring diet-microbiota interactions and therapeutic nutrition management in inflammatory bowel disease - Wang, Xinran; Wang, Yiran; Sun, Lulu (Biophysics reports, 2025)
Intestinal bowel disease (IBD) is a chronic, early-onset, recurrent gastrointestinal immune-related disease that has become globalized. Although the combination of genetic, environmental, and immunological factors leads to intestinal inflammation and barrier damage, the etiology of IBD is not clearly defined. In recent years, diet-microbiota interactions have been widely studied for their potential in pathogenesis and treatment for IBD. Meanwhile, the significant efficacy of exclusive enteral nutrition (EEN) has been observed in clinical practice with modulation in gut microbiota, but the specific mechanisms and optimization measures remain challenging. Therefore, we first describe the development of existing microbial research techniques and the perspectives that can be broadened. We then synthesize findings on how dietary components impact IBD progression and treatment through microbiota. Finally, based on correlating clinical and basic experiments, we summarize the current status and potential mechanisms of EEN for treating IBD, especially the contradictory points encountered in its application.